2016
DOI: 10.5897/jabsd2016.0261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rootstock type and scion cultivar on apple leaf total nitrogen in Chencha, GamoGofa zone, Southern Ethiopia

Abstract: ), while Jonica, Royal Gala, and BR was below the range. In evaluate of rootstock and scion interaction distinguished rootstock type and scion cultivar have influence on leaf total N concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In agreement with this, Roy and George (1987) revealed that, rootstocks profoundly affect water and nutrients uptake from the soil especially nitrogen which is of prime importance as it affects the photosynthetic rate, production of carbohydrates and proteins, which in turn control plant growth and development. Kebede and Sabura (2016) showed that influence of the rootstocks on nitrogen (N) content in the petioles was significant.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this, Roy and George (1987) revealed that, rootstocks profoundly affect water and nutrients uptake from the soil especially nitrogen which is of prime importance as it affects the photosynthetic rate, production of carbohydrates and proteins, which in turn control plant growth and development. Kebede and Sabura (2016) showed that influence of the rootstocks on nitrogen (N) content in the petioles was significant.…”
Section: Introductionmentioning
confidence: 99%